Experimental investigation on potential of a concentrated photovoltaic-thermoelectric system with phase change materials. (1st March 2017) - Cui, Tengfei; Xuan, Yimin; Yin, Ershuai; Li, Qiang; Li, Dianhong
Abstract: Since the influence of temperature on the conversion efficiencies of photovoltaic (PV) cells and thermoelectric (TE) generators are totally different and opposite, the system operating temperature becomes a key parameter which significantly determines the utilization efficiency of the common PV-TE system on solar energy. In order to make the PV-TE system obtain higher energy utilization efficiency, phase change material (PCM) is incorporated to construct a novel PV-PCM-TE hybrid system to maintain the system operating at the ideal working temperature. The performance of such a novel hybrid system is experimentally studied corresponding to a number of practical working conditions. The temperature, efficiency, and output power of the hybrid system are compared with those of the pure PV system under the same circumstance. The effects of the optical concentrations ratio and cooling approaches on the conversion efficiency of the hybrid system are experimentally investigated. The whole conversion efficiencies of the hybrid system incorporated with TE generators with different values of dimensionless thermoelectric coefficient (ZT) are discussed. The present work reveals that such a hybrid system possesses a promising potential on the full-spectrum utilization of solar energy. Highlights: An experimental PV-PCM-TE device is constructed and compared to the pure PV system. The performances of hybrid system under practical working conditions are studied. The PV-PCM-TE system is proved to have higher efficiencies than the pure PV system. The cost and influence parameters of the PV-PCM-TE system are investigated.